Estudio de factibilidad para fabricar un ladrillo ecológico de colillas de cigarrillo en la ciudad de Tunja, Boyacá (2022)
Through this feasibility study, an option is presented to collect cigarette butts in this way in the manufacture of a mass-use product such as brick, with the main objective of knowing if it is feasible to manufacture this product according to the market. current